The Effect of Customer Relationship Management on Customer Loyalty at Chat Barber Banjarmasin - Orion Yoga Pratama; Sugiharto; M. Hasanur Arifn; Setio Utomo (Journal of Business Transformation and Strategy, 2025)
This study aims to examine the partial effect of Customer Relationship Management on customer loyalty at Chat Barber Banjarmasin. This research employs a quantitative approach. The sample consists of 71 Chat Barber customers who met the predetermined criteria, selected using a non-probability sampling technique, namely incidental sampling. Data were collected through questionnaires, and data analysis was conducted using simple linear regression analysis. The results indicate that Customer Relationship Management (CRM) has a significant partial effect on customer loyalty